2023
DOI: 10.3390/separations10040241
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Variability of Azorean Cryptomeria japonica Leaves under Different Distillation Methods, Part 2: Molluscicidal Activity and Brine Shrimp Lethality

Abstract: This study reports on the in vivo molluscicidal activity and Artemia salina lethality of Azorean Cryptomeria japonica leaf (CJL) essential oils (EOs) obtained by hydrodistillation (HD) and water-steam distillation (WSD) techniques, especially in light of the recent focus on the use of forestry and wood industry residues in a sustainable world economy. Molluscicidal activity was performed during several life stages of Radix peregra by the immersion method, under laboratory conditions. A first screening through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Previous research by the authors on Azorean C. japonica EO, intended to improve the commercial value of this eco-friendly natural product, revealed that their composition and bioactivity are influenced by the different distillation methods used [10,17]. In addition, in our earlier study [8] on the biological properties of EOs extracted via hydrodistillation (HD) from different parts of Azorean C. japonica, we observed that FC EO was the most promising source of multi-bioactivities.…”
Section: Introductionmentioning
confidence: 79%
“…Previous research by the authors on Azorean C. japonica EO, intended to improve the commercial value of this eco-friendly natural product, revealed that their composition and bioactivity are influenced by the different distillation methods used [10,17]. In addition, in our earlier study [8] on the biological properties of EOs extracted via hydrodistillation (HD) from different parts of Azorean C. japonica, we observed that FC EO was the most promising source of multi-bioactivities.…”
Section: Introductionmentioning
confidence: 79%
“…In addition, monoterpene hydrocarbons dominated in Azorean C. japonica leaf EO, while oxygen-containing sesquiterpenes are the major terpene fraction in C. japonica leaf EOs from East Asia countries [7]. Concerning the biological activity of Azorean C. japonica leaf EO, previous investigations revealed their potential as a natural biocide, namely as a bactericide, fungicide [13], and molluscicide against Radix peregra (Müller), which is a crucial vector of fascioliasis, a disease with a high impact on public health, as well as on animal production losses and consequent economic costs [14]. Many other bioactivities of C. japonica leaf EO samples from other countries have been reported, including analgesic, anti-inflammatory, antimelanogenesis, antioxidant, an-titussive, antiulcer, anxiolytic, cancer chemopreventive, neuropharmacological, whitening, antitermite, mosquito larvicidal, mosquito repellent, and silverfish repellent properties ( [11] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…high impact on public health, as well as on animal production losses and conseq economic costs [14]. Many other bioactivities of C. japonica leaf EO samples from countries have been reported, including analgesic, anti-inflammatory, antimelanogen antioxidant, antitussive, antiulcer, anxiolytic, cancer chemopreven neuropharmacological, whitening, antitermite, mosquito larvicidal, mosquito repe and silverfish repellent properties ( [11] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…However, these C. japonica biomass residues (CJBR) are still raw materials that can be converted into value-added products, such as EOs. In fact, the EOs extracted from different CJBR (mainly leaves, bark, and heartwood) exhibit several bioactivities, including molluscicide, mosquito larvicidal, mosquito repellent, termiticidal, antibacterial, antifungal, and neuropharmacological effects, namely anxiolytic, analgesic, and soothing properties [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%